The outcomes of nonsurgical periodontal therapy: a retrospective study - Husain, Juzaily; Yaacob, Munirah; Mohd, Farah Natashah; Badrul Hisyam, Balqis Hazirah; Mohd Saleh, Liyana (Wolters Kluwer Medknow Publications, 2020)
Aim: In this study, patients with chronic periodontitis (CP) were evaluated to determine the clinical outcomes following nonsurgical periodontal therapy. Materials and Methods: A retrospective assessment of clinical outcomes following nonsurgical periodontal therapy was provided by International Islamic University Malaysia (IIUM) dental undergraduates. This secondary data analysis of 110 patients with chronic periodontitis were reviewed and clinical data abstracted. Data were analyzed to observe the treatment outcomes of all patients and then were grouped into “responders” or “nonresponders” to assess the correlation between clinical prognostic indicators and the treatment outcome. Results: Significant improvements with all clinical parameters such as plaque score, bleeding on probing (BOP), periodontal probing depth (PPD) >4 mm and >6 mm, and clinical attachment loss were noted on all patients. Deep sites (PPD >4 mm) were significantly higher in smokers and it continued to be in large proportions during the posttreatment period. A great number of smokers and all diabetic patients fall into the nonresponder group. However, this study fails to statistically prove better outcomes in terms of all clinical parameters on the responder group as compared to the nonresponder group as all P values > 0.05. Conclusion: The CP treatments were positively associated with the benefits of nonsurgical therapy by IIUM undergraduates. It is displayed by the improvement in all clinical parameters. In addition, poorer outcomes were portrayed by smokers as reduction of BOP and PPD was not significantly achieved compared to their counterparts. However, patient-specific outcomes were not positively reported due to lack of data.